PENERAPAN PERATURAN, PEMAHAMAN, DAN PERILAKU HUKUM TENTANG KESEHATAN DAN KESELAMATAN KERJA (K3) DI POLITEKNIK AKAMIGAS PALEMBANG - Noviansyah, KA. Azizi; Dea Justicia Ardha (Jurnal Cakrawala Ilmiah, 2023)
Legal protection of the labor force one of them is given in the form of occupational health and safety guarantees that must be accommodated by the institution where the work. Only in practice, such legal protections are sometimes not followed by the management of the institution. System safety management and occupational health that must be met by companies regulated in Government Regulation 50 Year 2012. In it regulates the obligation istitusi education providing education that could endanger safety and health. Therefore, should Polytechnic Palembang AKAMIGAS carry out the implementation of occupational health and safety regulations properly. Therefore, the issue raised in this study were: 1). How the application of occupational safety and health regulations in AKAMIGAS? 2). How the behavior of labor law relating to occupational safety and health in AKAMIGAS? 3). How does an understanding of labor associated with occupational safety and health in AKAMIGAS? The method used is the method of empirical research or non-doctrinal. Research thus view the law has a relationship with the community in a certain pattern. Therefore methods to obtain the necessary data in addition to the literature study is to interview and participant observation.. The results showed that the adoption of occupational safety and health regulations at the Polytechnic AKAMIGAS Palembang examined from the aspect of substance, structure, and culture. From the aspect of substance, the policy to implement the occupational safety and health regulations have been established. Only, in the context of reform and policy evaluation to date has not done. In addition, if based on the substance of the law, fulfillment facilities and infrastructure in accordance with the substance of the policy has been implemented by stakeholders Polytechnic AKAMIGAS Palembang, however, have not done the calculations carefully about a range of facilities and infrastructure of health and safety in case of occupational accidents or certain events (fires and others). In terms of structure, the lack of structure in charge of occupational safety and health matters in particular be shortcomings in the application of rules K3 at the Polytechnic AKAMIGAS Palembang. In terms of culture, the culture of labor at the Polytechnic AKAMIGAS yet fully prioritize culture of safe practices (smoking in a place that should be forbidden to smoke, and others). Then Behavior employment law relating to occupational safety and health at the Polytechnic AKAMIGAS Palembang showed indications of non-compliance related to the management requirements for safety and health so as to bring harmful effects to the workforce. In addition, there are unsafe condition which could lead to accidents, ie with never done testing the viability of infrastructure health and safety based on certain standards. Further understanding of the labor associated with occupational safety and health at the Polytechnic Palembang respective AKAMIGAS very less, this is because the system has not been established safety and health management established. In addition, an understanding of health and safety is still a comprehension of facilities and infrastructure without reviewing occupational safety and health which include; research on the study, research on working equipment, and so forth.